Rota Virus Gastroenteritis in Children Upto Five years of Age - Ayesha Afzal , Parveen Akhtar Tariq,Shehla Choudhry, (Journal of Rawalpindi Medical College, 2010)
Background: To estimate the proportion and peak age of rotavirus diarrhoea among children of age two months to five years Methods: In this descriptive study five hundred patients with acute watery diarrhoea (AWD) were screened for rotavirus. Stool sample of about 5 ml was taken & tested in the laboratory for group A rotavirus antigen by Enzyme immunoassays (EIA). Results: Mean age of patients with AWD was 12.5 months . Out of 500 patients 147 ( 29.4%) were positive for group A rotavirus. Majority of positive patients 116/147 (78.9%) were in the age group 2 months to 12 months. Conclusions: As there are many types of rotavirus i.e. A, B, C, D, and E so overall burden for all serotypes will be much higher. Rotavirus vaccine is an effective preventive measure available against rotavirus diarrhea